Interspecific somatic hybrids enriching potato gene pool - Tiwari, Jagesh K; Poonam, Poonam; Devi, Sapna; Ali, Nilofer; K tuthra, S K; Singh, R K; Kumar, Vinod; Bhardwaj, Vinay; Chakrabarti, S K (Indian Horticulture, 2019)
The scientists of our Shimla-based ICAR institute have produced interspecific potato somatic hybrids via protoplast fusion between cultivated tuber-bearing Solanum tuberosum dihaploid clone ‘C-13’ and non-tuberous diploid wild S. etuberosum species for resistance to potato virus Y (PVY). These somatic hybrids are tetraploid, male fertile, PVY resistant, having diverse cytoplasm type wider genetic base. Therefore, these somatic hybrids have immense potential for uses in potato breeding via conventional-cum-molecular breeding methods to widen the gene pool of cultivated potato by introgression of genes from wild Solanum species, says Dr S K Chakrabarti, Director, CPRI, Shimla.